Fiscal decentralization and health service delivery: An assessment - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2020)
More than 25 years into the implementation of the Local Government Code of 1991, it is inconclusive whether fiscal decentralization indeed improves health service delivery in the Philippines. There is lack of studies that employ rigorous quantitative approach to address the research issue at hand. In this regard, the study attempts to contribute to the small body of literature and motivate further research and generation of reliable data that are crucial for evidence-based/informed policymaking. In particular, the study proposes an analytical framework that examines the effects of fiscal decentralization on health service delivery using difference-in-differences (DID) method. It draws up the standard measure of the extent/degree of fiscal decentralization affecting the health sector. Such endeavor is the first ever attempt to measure the extent/degree of health devolution in the Philippines, i.e., in terms of the health expenditure decentralization ratio. The output variables of interest include access to safe water and sanitation, health facility-based delivery, and access to hospital inpatient services. The control variables include two measures of fiscal decentralization to account for financial/fiscal autonomy of the local government units (LGUs) on the income side (i.e., the ratio of LGU own-source revenue to LGU expenditures and ratio of LGU own-source revenue to LGU income); LGU health spending as a proportion of total LGU expenditures; and per capita LGU income. The choice of variables was constrained by unavailability of disaggregated data at the LGU level. [...]
Keywords: 330; health devolution; devolution; fiscal decentralization; decentralization; and difference-in-differences (DID) analysis/method